[Sjogren’s syndrome] - Witte, T. (Z Rheumatol, 2019)
The prevalence of primary Sjogren’s syndrome (pSS) is between 1:100 and 1:1000 and it is therefore the most common connective tissue disease. Nevertheless, it can be difficult to diagnose pSS as the symptoms are frequently unspecific and diagnostic markers are lacking in many patients. In addition, only few controlled therapeutic studies of pSS have been carried out so that the optimal management is not yet clear. Meanwhile, outcome parameters to monitor clinical improvement have been developed and a large number of therapeutic studies are currently being performed. This review article summarizes the current diagnostic and treatment options for pSS.